ChemInform Abstract: Oxidant‐Resistant Hydrogen‐Bond‐Donating Organocatalyst for Enantioselective Nucleophilic Epoxidation of α, β‐Unsaturated Amides. Issue 45 (23rd October 2014) - Kobayashi, Yusuke; Li, Shanji; Takemoto, Yoshiji
Abstract The bifunctional benzothiadiazine‐based organocatalyst promotes the asymmetric epoxidation of α, β‐unsaturated amides to provide chiral oxiranecarboxamides in excellent yields and low to good enantioselectivities.